Hemoglobin Siam α215argβ2: A new α-chain variant - Sa nga Pootrakul (2018)
A 28-year-old, healthy male of chinese ancestry with normal hematologic findings was found to have an abnormal hemoglobin moving more slowly than hemoglobin F in starch gel electrophoresis. The relative amounts of the abnormal component, hemoglobin A 2 and slow hemoglobin A 2 , as determined by cellulose acetate electrophoresis, were 15.2, 1.64, and 0.56% respectively. The hemoglobin chain dissociation by p-chloromercuribenzoate treatment confirmed that it was an α-chain variant. The abnormal globin chain was fractionated by carboxymethyl cellulose chromatography. Peptide mapping revealed that the amino acid alteration occurs in αTp III (tryptic peptide No. 3, residues 12 to 16 of the α-chain). Special stains and amino acid analyses of the abnormal peptide indicated that glycine at residue 15 was replaced by arginine, and the hemoglobin is thus α 2 15arg β 2 . Since the mutation has not been previously described, it is proposed that it be called "Hemoglobin Siam". © 1974 Springer-Verlag.